THE OPPOSITIONAL BINARIES IN THE POETRY OF IBN AL-ABBĀR AL-BALANSĪ – “YOUTH AND OLD AGE” AS A MODEL - نصرالدين أنديرا; حسين محمد (Humanities Journal of University of Zakho, 2026)
The poet is a sensitive being, easily affected, expressing emotions through harmonized words and phrases adorned with the vibrations of his soul and the stirrings of his feelings. Poetry for the most part, is lyrical, painting with words the depths of the Arab individual, filled with accumulated experiences and emotions resulting from both individual and collective suffering throughout time, life, and society. These include joy and sorrow, bliss and pain, wealth and poverty, stability and loss, love and hatred… and other such contradictions experienced by every human being. A close reading of Ibn al-Abbār al-Balansī’s poetry reveals a clear manifestation of oppositional binaries within his poems, carrying deep connotations that reflect a life filled with hardships, travels, challenges, and betrayals — whether in the psychological, intellectual, or social realms. He employs these realities through polar oppositions: sadness/joy, good/evil, truth/falsehood, light/darkness, love/hatred, dignity/humiliation, compassion/cruelty. His poetry also embodies bravery/cowardice, hope/despair, and fear/security. Through this, he expresses a longing for knowledge and a passion for politics, distinguishing himself in his poetic craft. His works offer rich aesthetic dimensions and fruitful semantic variety, granting his poetry unique artistic layers and profound philosophical visions that reflect existential anxiety. This is achieved through the active presence of cultural patterns that reveal the hidden and bring forth the concealed. Therefore, this study will undertake a careful analysis of the binary opposition of youth and old age in his poetic texts, uncovering the underlying meanings behind this duality in its various dimensions — meanings that stirred within the poet feelings of fear and, at times, sorrow about the fate that awaits all who cherish life and hold long hopes within themselves.